2019
DOI: 10.21203/rs.2.9605/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Escherichia Coli O157:H7: Distribution, molecular characterization, antimicrobial resistance patterns and source of contamination of sheep and goat carcasses at an export Abattoir, Mojdo, Ethiopia

Abstract: Background : Cattle have been identified as a major reservoir of E. coli O157:H7 for human infection; the ecology of the organism in sheep and goats is less understood. This study was carried out to determine prevalence, source of infection, antibiotic resistance and molecular characterization of Escherichia coli O157: H7 isolated from sheep and goat. Methods : Systematic random sampling was carried out at Modjo export abattoir, Ethiopia, from November 2012 to April 2013 to collect 408 samples from 72 sheep an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 13 publications
(16 reference statements)
1
14
0
Order By: Relevance
“…In Ethiopia, a country which ranks second after Nigeria in the health burden of zoonotic diseases in Africa [28], the epidemiology of food-borne pathogens especially that of pathogenic E. coli is not well studied. However, recently, there is an increasing trend of reporting the occurrence level of the organism in beef, dairy products, and fish [2,3,9,16,[29][30][31][32][33][34][35][36][37]. Besides this, current and detailed studies on the prevalence of antibiotic resistance and multidrug phenotypes of enterohemorrhagic E. coli O157 : H7 in foods of animal origin in different catering establishments are very limited in Ethiopia except for the report of [2,3,9] on beef at butcher shops and restaurants and raw milk and dairy products such as yogurt and cheese derived from raw milk at cafeterias, restaurants, open markets, and supermarkets in Central Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, a country which ranks second after Nigeria in the health burden of zoonotic diseases in Africa [28], the epidemiology of food-borne pathogens especially that of pathogenic E. coli is not well studied. However, recently, there is an increasing trend of reporting the occurrence level of the organism in beef, dairy products, and fish [2,3,9,16,[29][30][31][32][33][34][35][36][37]. Besides this, current and detailed studies on the prevalence of antibiotic resistance and multidrug phenotypes of enterohemorrhagic E. coli O157 : H7 in foods of animal origin in different catering establishments are very limited in Ethiopia except for the report of [2,3,9] on beef at butcher shops and restaurants and raw milk and dairy products such as yogurt and cheese derived from raw milk at cafeterias, restaurants, open markets, and supermarkets in Central Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Most of E. coli are normal inhabitants of the gastrointestinal tract (lower ileum and large intestine) of animals and humans [23,131,132], while others are pathogenic to humans [133]. E. coli are of zoonotic in nature and constitute a public health hazard [134].…”
Section: Escherichia Coli Ementioning
confidence: 99%
“…is strain is an important emerging food-borne pathogen of humans causing outbreaks worldwide [3,138]. Outbreaks have been reported from different countries of the world including the United States, Canada, Asia, Australia, Europe [23], and different African countries, stretching from South to East and West parts of the continent [131]. It has been indicated that an estimated 74,000 cases and 61 deaths annually are attributable to E. coli O157:H7 in the USA [17].…”
Section: Escherichia Coli Ementioning
confidence: 99%
See 2 more Smart Citations